Applied Biosystems VeriFiler Plus PCR Amplification Kit with internal quality control system provides confident answers with challenging forensic samples. Issue 1 (December 2019) - Zhong, Chang; Green, Robert; Norona, Wilma; Mulero, Julio; Eardley, Rob; Ge, Jianye; Lackey, Angie
Abstract: The Applied Biosystems™ VeriFiler™ Plus PCR Amplification Kit has been developed to meet challenging forensic casework needs globally. It is a companion kit to the Applied Biosystems™ VeriFiler™ Express PCR Amplification Kit for databasing. Powered by a six-dye short tandem repeat (STR) chemistry and an improved master mix formulation, this kit is specifically designed for challenging sample types—touch, degraded, or inhibited samples with improved sensitivity and enhanced robustness against inhibition. With an recommended input of 0.5 ng, the VeriFiler Plus kit targets a total of 25 loci- 23 autosomal STRs, including the core CODIS loci, Penta D, Penta E and D6S1043, 2 gender discrimination markers, while also including an internal quality control (IQC) system. The IQC system contained in the VeriFiler Plus kit consists of two synthetic sequences with specific primers for each of the targets. This system provides positive confirmation that all assay components are functioning as expected. This system is particularly useful for confirming the validity of negative results and distinguishing samples that are degraded from those that contain PCR inhibitors.